2015
DOI: 10.18186/jte.95418
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Exergy and Sustainability Analysis of Two-stage Vapour Compression Refrigeration System

Abstract: In this paper comparative analysis of R152a, R600, R600a, R410a, R290, R1234yf, R404a and R134a as refrigerants in two stage vapour compression refrigeration system has been done on the basis of energetic and exergetic performance. Performance parameters such as entropy generations, COP, exergetic efficiency, sustainability index were investigated at different ambient condition. It was found that both energy and exergy efficiencies of R134a is 8.97% and 5.38% lower than R152a and R600 respectively at -50 o C e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
(19 reference statements)
0
11
1
4
Order By: Relevance
“…The e®ect of evaporator temperature on COP of two-stage VCR system using various refrigerants has been demonstrated in Fig. 3 following the work of Chopra et al 2 and Khan et al 16 The¯gure shows that COP increases with the increase in evaporator temperature. This is due to the fact that pressure ratio across each stage decreases with evaporator temperature and this results in increase in COP of the system.…”
Section: E®ect Of Evaporator Temp On Copmentioning
confidence: 89%
See 2 more Smart Citations
“…The e®ect of evaporator temperature on COP of two-stage VCR system using various refrigerants has been demonstrated in Fig. 3 following the work of Chopra et al 2 and Khan et al 16 The¯gure shows that COP increases with the increase in evaporator temperature. This is due to the fact that pressure ratio across each stage decreases with evaporator temperature and this results in increase in COP of the system.…”
Section: E®ect Of Evaporator Temp On Copmentioning
confidence: 89%
“…The e®ect of condenser temperature on exergy loss for a two-stage VCR system using various refrigerants has been demonstrated in Fig. 5 based on the results of Chandrasekharan 6 and Chopra et al 2 It can be observed from the¯gure that with the increase in condenser temperature, exergy destruction or loss increases and the loss is more with R290 compared to R600a and 134a.…”
Section: E®ect Of Condenser Temperature On Exergy Lossmentioning
confidence: 95%
See 1 more Smart Citation
“…Within the above mentioned chapters to the students are introduced information regarding international Current Legislation and refrigerant selection. The main resulting aspects are as below [2], [3], [4], [5], [6], [7], [8] and [9]. The ozone layer is of major importance for the Earth's surface and people's health.…”
Section: Course Compliance With the Request Of Industrymentioning
confidence: 99%
“…The results show that inter-stage pressure should be more considered in the areas with higher daily temperature. Two-stages VC refrigeration cycle has been analysed by using energy, exergy and sustainability concept [5]. Multistage VC refrigeration cycle has been optimized using general staging model [6].…”
Section: Introductionmentioning
confidence: 99%